Main‐Chain Polyimidazolium Polymers by One‐Pot Synthesis and Application as Nitrogen‐Doped Carbon Precursors. Issue 18 (21st March 2017) - Grygiel, Konrad; Kirchhecker, Sarah; Gong, Jiang; Antonietti, Markus; Esposito, Davide; Yuan, Jiayin
Abstract : The Debus–Radziszewski reaction is used for the one‐pot synthesis of main‐chain imidazolium‐containing polymers from simple organic compounds. This paper finds that via anion‐metathesis reaction to replace the acetate anion with dicyanamide, the thermal properties of the main‐chain polyimidazoliums are improved and one of these polyimidazoliums presents an unusually high carbonization yield of up to 66 wt% at 900 °C. Abstract : This paper reports on the one‐pot synthesis of main‐chain imidazolium‐containing polymers, some of which show unusually high thermal stability. The imidazolium polymers are obtained by modified Debus–Radziszewski reactions for the chain build‐up from simple organic compounds, here pyruvaldehyde, formaldehyde, acetic acid, and a variety of diamines. The reactions are performed in aqueous media at ambient conditions, being synthetically elegant, convenient, and highly efficient. Finally, a simple anion‐metathesis reaction is conducted to replace the acetate anion with dicyanamide, and the thermal properties of the main‐chain polyimidazoliums before and after anion exchange are studied in detail, which demonstrate chain cross‐linking by the counterion and a coupled unusually high carbonization yield of up to 66 wt% at 900 °C.